2022
DOI: 10.3390/agronomy13010042
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency of Oat:Pea Intercrops Affected by Sowing Ratio and Nitrogen Fertilization

Abstract: This study analyzed energy input (direct and indirect), energy output, net-energy output, energy use efficiency, energy intensity, and the energy productivity of oat:pea intercrops as affected by sowing ratio (oat:pea (%:%): 100:0, 75:25, 50:50, 25:75, 0:100) and nitrogen (N) fertilization (0, 60, 120 kg N ha−1). The two year field experiment was conducted on a calcaric Chernozem soil in the north-western part of the Pannonian Basin. The results for grain yield showed that pure stands of oat and pea had a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other important measures affecting agrosystems are catch crops, which have the potential to ensure sustainable agriculture, support production diversification, reduce pest and pathogen pressure [38][39][40], improve soil health, optimize resource use [41,42] and increase biodiversity in fields [43]. Multispecies mixtures of catch crops maximize land use and increase biodiversity [44].…”
Section: Introductionmentioning
confidence: 99%
“…Other important measures affecting agrosystems are catch crops, which have the potential to ensure sustainable agriculture, support production diversification, reduce pest and pathogen pressure [38][39][40], improve soil health, optimize resource use [41,42] and increase biodiversity in fields [43]. Multispecies mixtures of catch crops maximize land use and increase biodiversity [44].…”
Section: Introductionmentioning
confidence: 99%
“…Energy consumption in agricultural systems is more pronounced in developed countries; thanks to widespread use of agricultural machinery. However, in developing countries due to the transition from traditional farming to mechanized agriculture, energy use also increases [3,4]. It is reported that using high yield cultivars, intensive farming systems, high application of fertilizers and pesticides and high level of mechanization resulted in high energy consumption in agronomical systems [5,6].…”
mentioning
confidence: 99%